ANALYSIS OF THE PERFORMANCE OF INDONESIAN MUTUAL STOCK FUNDS USING SHARPE, TREYNOR, JENSEN AND M2 METHOD PERIOD 2010 – 2019 - Andreas Andreas; Sautma Ronni Basana (International Journal of Financial and Investment Studies (IJFIS), 2021)
This study examines the performance of equity mutual funds using Sharpe, Treynor, Jensen, and M2. The sample used in this study is 57 stock mutual funds in 2015 – 2019 and 29 stock mutual funds in 2010 – 2019. The performance of stock mutual funds will be compared with LQ – 45 and IHSG to find out whether they underperform or outperform on market performance. The results showed that when seen in years 2015 - 2019 with the benchmark LQ - 45, 11 equity funds outperformed by using Sharpe, Treynor, and M2, and 12 mutual funds stocks outperformed by using a Jensen. Using the Composite Index as the benchmark, it is found that four equity funds outperformed by using Sharpe, M2, and 5 equity funds outperformed by using Treynor and Jensen from 57 samples of mutual fund shares. From the performance of the year 2010 - 2019, it is found that the 10 equity funds outperformed by using Sharpe and M2, and 15 equity funds outperformed by using Treynor and Jensen with LQ – 45 as the benchmark. The Composite Index found that 0 of stock mutual funds outperformed by using Sharpe and M2, while 3 mutual funds outperformed using Treynor and 2 mutual funds outperformed using Jensen from 29 stock mutual funds samples.